Family functionality, autonomy and psychosocial welfare in the elderly - Troncoso Pantoja, Claudia (2018)
Objective: To relate family functionality to autonomy and psychosocial welfare of elderly people living in the Huechuraba commune in Santiago, Chile, during the year 2016. Materials and methods: A descriptive, cross-sectional, correlational study with a purposive sample of 60 elderly volunteers who fulfilled the screening criteria. For data collection, the Family APGAR test, WHOQOL-BREF scale and Functional Assessment of the Elderly (EFAM) were used. For the analysis of the results, descriptive statistics and association tests such as chi-square and Mann-Whitney U test were used. Results: Over 70 % of the participants had very functional families and only 3 % belonged to severely dysfunctional families. Forty-five percent (45 %) of the participants were autonomous but at risk of being dependent and 16.7 % were at risk of being dependent. No relationship between family functionality and physical health was observed; however, there is an association between family functionality, psychological health and interpersonal relationships. Conclusions: There is a relationship between family functionality and level of autonomy, psychological health, interpersonal relationships and environment, because elderly people who belong to families with better internal dynamics enjoy a better quality of life.